Sustainability Focus in Destination Management. The Case of Russia - DEDUSENKO, Elena Aleksandrovna; WAGENSEIL, Urs (Journal of Environmental Management and Tourism; Vol 11 No 3 (2020): JEMT Volume XI Issue 3(43) Summer 2020DO - 10.14505//jemt.v11.3(43).04, 2020)
This paper analyzes the tourism management regarding sustainability of eight Russian regions and discusses the possibility of implementing the principles of sustainable tourism development in a particular region using the performance criteria of the Global Sustainable Tourism Council (GSTC). The goals of this paper are to focus on sustainable tourism development as a function of destination management and discuss the problems of the integrated efforts of Destination Management Organizations (DMOs) in the field of tourism and destination sustainability.